The Chain-Mediation Pathway of Social Avoidance to Depression in College Students Is Regulated by Self-Esteem - Yuan, Ye; Jiang, Suhua; Wen, Xi; Han, Zhong; Wu, Daili; Wang, Xuanping; Ye, Tingyang; Hu, Yimin; Jeong, Jaesik; Xiang, Min (Frontiers in Psychology, 2022)
Objective: Here, we investigated the relationship between social avoidance and depression in college students, explored the mediating roles of loneliness and trust, and the regulatory role of self-esteem, to provide a theoretical intervention approach based on internal mechanisms. Methods: Using a simple random overall sampling method, 1,021 college students were investigated using self-rating depression, social avoidance and distress, loneliness, interpersonal trust and self-esteem scales. Results: There was a significant positive correlation between social avoidance and depression. Loneliness and interpersonal trust played chain-mediating roles between social avoidance and depression. The influence of social avoidance on interpersonal trust was regulated by self-esteem. Specifically, the social avoidance level of the low self-esteem group was more likely to be affected by interpersonal trust issues. Conclusion: Social avoidance not only directly affects college students’ depression, it also has indirect effects through interpersonal trust and loneliness. Thus, interpersonal trust and loneliness have chain-mediating effects between social avoidance and depression in college students, and self-esteem regulates the mediation process.